2015
DOI: 10.1007/s00405-015-3504-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases and life events accounted for 2–18 % population attributable risks for adult hearing loss: UK Adult Psychiatric Morbidity Survey, 2007

Abstract: Links between chronic diseases and hearing loss in adults have emerged. However, previous investigations were not complete, and the role of life events was unclear. Therefore, it was aimed to examine the relationships of common chronic diseases and life events and adult hearing loss in a country-wide and population-based study. Data were retrieved from UK Adult Psychiatric Morbidity Survey, 2007, being cross-sectional, including demographics, self-reported prior health conditions and hearing loss (ever and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Chronic disease history was a reported physician diagnosis of hypertension, heart disease, angina, heart attack or diabetes at Wave 1 or Wave 2. These conditions have been associated with hearing loss [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Chronic disease history was a reported physician diagnosis of hypertension, heart disease, angina, heart attack or diabetes at Wave 1 or Wave 2. These conditions have been associated with hearing loss [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…OA is also the most common joint disease and is the major cause of pain and disability throughout the world (3). Previous studies have shown that the chronic diseases were associated with hearing loss in adults (4). In 2007, Rawool et al reported the higher prevalence of middle ear abnormalities in patients with OA compared to controls (1), however, little is known about auditory manifestations in patients with OA.…”
Section: Introductionmentioning
confidence: 99%